An Observational Study on the Use of Peripheral Intravenous Lines vs. Central Lines in a Neonatal Intensive Care Unit - Arieh Riskin; Adir Iofe; Donia Zidan; Irit Shoris; Arina Toropine; Rasha Zoabi-Safadi; David Bader; Ayala Gover (MDPI AG, 2022)
Background and Objectives: There is a debate regarding the preferred intravenous (IV) access for newborns. Our aim was to study practices regarding the choice of vascular access and outcomes. Methods: A seven-month prospective observational study on IV lines used in all newborns admitted to Bnai Zion Medical Center's neonatal intensive care unit (NICU). Results: Of 120 infants followed, 94 required IV lines. Infants born at ≤32 weeks gestation, or with a head circumference ≤29 cm were more likely to require two or more IV lines or a central line for the administration of parenteral nutrition or medications for longer periods. However, central lines (umbilical or peripherally inserted central catheters (PICC)) were not associated with better nutritional status at discharge based on weight z-scores. Only one complication was noted-a central line-associated bloodstream infection in a PICC. Conclusions: Our data suggest preferring central IV access for preterm infants born at ≤32 weeks or with a head circumference ≤29 cm. We encourage other NICUs to study their own data and draw their practice guidelines for preferred IV access (central vs. peripheral) upon admission to the NICU.